2022
DOI: 10.3390/ijerph19031789
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Periodontal Treatment on Clinical and Biological Indicators, Quality of Life, and Oral Health in Rheumatoid Arthritis Patients: A Quasi-Experimental Study

Abstract: Non-surgical periodontal therapy (NSPT) has been shown to have systemic effects. It has been suggested that, similar to rheumatoid arthritis (RA), periodontitis (PD) has an impact on general health, in terms of psychological, physical, and social aspects. This study determines the effect of periodontal treatment in RA activity, health-related quality of life, and oral health self-perception before and after periodontal treatment in RA patients. A quasi-experimental, prospective, non-randomized study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…It reflects changes at the physiological, psychological and social levels, and it also gives an insight into a person’s overall health status [ 52 , 53 ]. An adequate treatment performed brings a significant improvement in individuals [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It reflects changes at the physiological, psychological and social levels, and it also gives an insight into a person’s overall health status [ 52 , 53 ]. An adequate treatment performed brings a significant improvement in individuals [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results derive from the clinical study of Posada-Lòpez A: NSPT has a positive effect on only quality of life and self-reported health indicators (Oral Health Impact Profile-14 and Short Form Health Survey 36), ameliorating psychological distress, emotional role, and mental health. No significant changes are reported in DAS28 [108].…”
Section: The Effect Of Non-surgical Periodontal Treatment (Nspt) On R...mentioning
confidence: 89%
“…Periodontitis is characterized by the pathological loss of periodontal ligament and alveolar bone. 365 The disease involves complex interactions between specific bacterial pathogens and destructive immune responses. 365 , 366 In a model of periodontitis, a single intra-gingival injection of LPS results in the significant expression of NF-κB p65 and pro-inflammatory cytokines in gingival tissues after 14 h. This is accompanied by increased expression of COX-2 and iNOS, as well as elevated levels of cytokines TNF-α and IL-1β.…”
Section: Nf-κb Signaling In Human Diseasesmentioning
confidence: 99%
“… 365 The disease involves complex interactions between specific bacterial pathogens and destructive immune responses. 365 , 366 In a model of periodontitis, a single intra-gingival injection of LPS results in the significant expression of NF-κB p65 and pro-inflammatory cytokines in gingival tissues after 14 h. This is accompanied by increased expression of COX-2 and iNOS, as well as elevated levels of cytokines TNF-α and IL-1β. These changes are often associated with heightened nociceptive perception, supporting the involvement of NF-κB in the pathogenesis of periodontitis.…”
Section: Nf-κb Signaling In Human Diseasesmentioning
confidence: 99%